Streptococcal sex syndrome: a curious association between sex and cellulitis - Mário Bruno Santos; Rita Félix Soares; Filipe Basto (Elsevier, 2018)
Women undergoing pelvic lymphadenectomy and radiation therapy for gynaecological cancer are prone to acute and often recurrent cellulitis as a consequence of compromised lymphatic circulation. Vaginal intercourse can trigger the infection, a condition named streptococcal sex syndrome (SSS). We report a 63-year old female patient with a history of pelvic lymphadenectomy and radiation therapy for gynaecological cancer. She presented to the obstetrics/gynaecology department for vaginal haemorrhage during sexual intercourse the day before. Gynaecological examination was unremarkable but she was febrile and presented inflammatory signs on the abdomen and lower left limb. The diagnostic workup suggested cellulitis and intravenous antibiotics were initiated, with complete recovery. Blood cultures were positive for Streptococcus mitis/oralis. One month later, the infection recurred at the same location, promptly after sexual intercourse. Keywords: Cellulitis, Sex, Streptococcus, Lymphadenectomy